Electrical appliance retailing in China : the GOME story - Li, Ming (China MBA series., 2014)
This book takes a close look into GOME, China's leading electrical appliance supplier famous for its stunning market shares and performance. The book is divided into five parts, organized according to an order of events, and it provides an in-depth analysis on the structure of GOME, its key managers, and the significant changes they implemented. In addition, the book captures the changes forced upon GOME after its president was imprisoned. (Series: Cases in Modern Chinese Business).